Differences in aerobic and anaerobic parameters between handball players on different playing positions - Milanovic, L.; Vuleta, D.; Vucetic, V. (Acta Kinesiologica, 2015)
The aim of this study was directed to analysing the differences in functional ability parameters of top handball players on different playing positions. The subject sample consisted of 70 handball players (25 wing players, 25 backcourt players, and 20 pivots) from the Croatian Division I Handball League. Statistically significant differences were found between handball players on different playing positions in parameters for the measurement of aerobic capabilities, while the analysis of the differences in anaerobic capacities showed no statistically significant differences. Significant differences in aerobic abilities could be explained by the morphologic differences of players on different playing positions and by different tasks that the players on different playing positions have during the match. Probably, it would be important to further examine the playing positions in handball in more detail and to use specific tests for the easurement of motor and functional abilities with a view to getting a deeper insight into the specific requirements of each playing position in handball.